2020
DOI: 10.1371/journal.pone.0239856
|View full text |Cite
|
Sign up to set email alerts
|

Association of the cyclooxygenase-2 1759A allele with migraine in Chinese Han individuals

Abstract: Cyclooxygenase-2 (COX-2) is known to be involved in the pathogenesis of migraine, and some polymorphisms are known to affect the expression of COX-2. This retrospective casecontrol study aimed to explore the associations between the-765 G>C (rs20417),-1759 G>A (rs3218625), and-8473 C>T (rs5275) COX-2 polymorphisms and migraine in Chinese Han individuals. One hundred and ten unrelated Han Chinese patients with migraine and 108 healthy controls were recruited between 03/2014 and 08/2016 at the First Affiliated H… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 43 publications
0
1
0
Order By: Relevance
“…4B). It has been reported that there is no signi cant relationship between migraine and this polymorphism in that area (Guan et al, 2020). Considering these results, we carried out this study among Iranian migraineurs to examine the associations of migraine, depression, and nausea with the COX-2-8473T > C (rs5275) polymorphism.…”
Section: Functional Analysis Of the Up-regulated Genes In Depressionmentioning
confidence: 95%
“…4B). It has been reported that there is no signi cant relationship between migraine and this polymorphism in that area (Guan et al, 2020). Considering these results, we carried out this study among Iranian migraineurs to examine the associations of migraine, depression, and nausea with the COX-2-8473T > C (rs5275) polymorphism.…”
Section: Functional Analysis Of the Up-regulated Genes In Depressionmentioning
confidence: 95%